Effect of Lactobacillus paracasei LK01 on Growth Performance, Antioxidant Capacity, Immunity, Intestinal Health, and Serum Biochemical Indices in Broilers - Weixin Liu; Hong Cheng; Hao Zhang; Guozhen Liu; Xinyu Yin; Cheng Zhang; Runsheng Jiang; Zaigui Wang; Xiaoling Ding (Animals)
This study aimed to investigate the effects of adding L. paracasei LK01 to the diet on the growth performance, antioxidant capacity, immunity, intestinal health, and serum biochemical indicators of broilers. This study selected 1080 one-day-old broiler chickens with similar body weight, and randomly divided them into six groups, with six replicates in each group and 30 chicks in each replicate. The chicks were fed (1) the basal diet (CON), (2) the basal diet with 106 CFU/kg L. paracasei LK01(T1), (3) the basal diet with 107 CFU/kg L. paracasei LK01(T2), (4) the basal diet with 108 CFU/kg L. paracasei LK01(T3), (5) the basal diet with 109 CFU/kg L. paracasei LK01(T4), and (6) the basal diet with 1010 CFU/kg L. paracasei LK01(T5). The experiment lasted for 42 days. In this study, compared with the CON group, the diet supplemented with L. paracasei significantly increased body weight from 1 to 21 days (p < 0.05). In addition, the 106 CFU/kg L. paracasei LK01 group significantly reduced the activity of glutamic oxaloacetic transaminase and triglyceride levels; the 107 CFU/kg,108 CFU/kg, and 109 CFU/kg L. paracasei LK01 groups also reduced serum uric acid and total cholesterol levels (p < 0.05). The experimental groups all had lower serum levels of malondialdehyde and interleukin-1β (p < 0.01). Except for the 106 CFU/kg group, all experimental groups had significantly lower tumor necrosis factor-α, and the 106 and 107 CFU/kg groups had higher immunoglobulin M levels (p < 0.05). In addition, the 106 CFU/kg group significantly reduced the depth of the ileocecal crypts and increased the villus-to-crypt ratio (V/C) of the jejunum and ileum. In addition, dietary supplementation with L. paracasei LK01 did not change the α diversity of the microbial community in the cecum, but significantly increased the proportion of Bacteroides (phylum) (p < 0.05). The 106 CFU/kg group also significantly increased the abundance of beneficial bacteria such as Ruminococcaceae (genus), Lachnospiraceae (genus), and Faecalibacterium (genus) (p < 0.05). In summary, this study revealed that adding 106 CFU/kg of L. paracasei LKO1 to broiler diets can improve their production performance, serum biochemical indicators, antioxidant, and immune capabilities, as well as cecal flora.